The Idea of (Re)Amending the Constitution of Year 1945 (A Proposition to Strengthen the Power of DPD and Judiciary) - Ni’matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2008)
The urgency of re-amending the Constitution of Year 1945 is due to the idea of enhancing the previous amendment, that is, to attain better administrative governance in Indonesia. As it goes without saying that the Constitution of Year 1945 is sacred, the amendment itself should be a well thought-out process that requires thorough and deep considerations and certainly cannot be taken carelessly.Keywords: Amendment of The Constitution of Year 1945, The Regional Repre¬sentatives Council (DPD), The Authority of Judiciary.